Briquitar' para viver: um estudo sobre a dependência e a exploração - Prado, Jackson Emanuel Benevides (1991)
The modernization process of the cacao crop developed in the cocoa producing region of the State of Bahia has started in the 1930's and was conso1idated in the 1970's, as a strategy of capitalism penetration in the rural communities and the strengthening of the Brazilian economic model. In spite of its limitations, this process has brought striking economic, political and social results to the regional rural society. Based on technical and economic criteria, this process was characterized by a strong ideological bias. It was supported by the idea that the growth of the revenues obtained by the farmers through the substitution of old agricultural techniques in cacao cultur,e and through the elevation of the cultural level of the farmers would brings new habits, new attitudes and the creation of a modern idea. In these circunstances, the education plays an important role in the modernization process and in the formation of social representations of the low rural social classes, which are the main subject of this study. The educative practices are considered as a result of this process and the social representation are characterized by its dependence, acquiescence and submission as well as manifestation of social consciousness even though, dissociated from a more concrete social practice.